Cell response of Antarctic strain Penicillium griseofulvum against low temperature stress - Krumova, Ekaterina Ts.; Koeva, Ekaterina K.; Stoitsova, Stoyanka R.; Paunova-Krasteva, Tsvetelina S.; Stoyancheva, Galina D.; Angelova, Maria B. (Polish Polar Research, 2021)
During the evolution organisms are subjected to the continuous impact of environmental factors. In recent years an increasing number of studies have focused on the physicochemical limits of life on Earth such as temperature, pressure, drought, salt content, pH, heavy metals, etc. Extreme environmental conditions disrupt the most important interactions that support the function and structure of biomolecules. For this reason, organisms inhabiting extreme habitats have recently become of particularly great interest. Although filamentous fungi are an important part of the polar ecosystem, information about their distribution and diversity, as well as their adaptation mechanisms, is insufficient. In the present study, the fungal strain Penicillium griseofulvum isolated from an Antarctic soil sample was used as a study model. The fungal cellular response against short term exposure to low temperature was observed. Our results clearly showed that short-term low temperature exposure caused oxidative stress in fungal cells and resulted in enhanced level of oxidative damaged proteins, accumulation of reserve carbohydrates and increased activity of the antioxidant enzyme defence. Ultrastructural changes in cell morphology were analysed. Different pattern of cell pathology provoked by the application of two stress temperatures was detected. Overall, this study aimed to observe the survival strategy of filamentous fungi in extremely cold habitats, and to acquire new knowledge about the relationship between low temperature and oxidative stress.